If It Were Only That Easy: The Use of Meta-Analytic Research by Organizational Scholars. (October 2019) - DeSimone, Justin A.; Köhler, Tine; Schoen, Jeremy L.
This paper evaluates how researchers are currently citing meta-analytic results and provides specific recommendations for interpreting the information provided by meta-analysis (MA). The past four decades have seen a proliferation of MA research across the organizational sciences and myriad improvements to how MA is conducted. MAs are cited more frequently than individual primary studies and have a substantial influence on subsequent research and theorizing. Yet the consumption of meta-analytic results in organizational scholarship remains superficial. We evaluate citation practices for four seminal MAs and find that authors predominantly interpret meta-analytic findings in the simplest way possible: as evidence of the existence of a relationship between variables. In focusing only on this basic finding, citing authors neglect the complexity and rich detail provided by MA. We offer advice for how researchers can more effectively leverage the strengths of meta-analytic findings to inform subsequent research by taking advantage of the benefits that meta-analytic methodology can provide for the explanation of organizational phenomena.